Discussion on the Value of Nanomaterial Strength during the Renovation and Strengthening of Ancient Wooden Structures. Issue 1 (4th May 2021) - Zhang, Boyang; Shi, Lei; Fan, Jinyu
Abstract: Although experts at home and abroad have done a lot of research on the performance of ancient wooden structures and seismic reinforcement, and have achieved many results, due to the complexity of its mechanical properties and the particularity of seismic reinforcement design, currently it is the research still lacks completeness and systematicness. The purpose of this article is to observe and analyze the strength of nanomaterials during the repair and reinforcement of ancient wooden structures, analyze the role of nanomaterials during the repair and reinforcement of ancient wooden structures, and understand the impact of nanomaterials on the strength and repair of ancient materials. A comparative analysis of the strength values, to explore the strength of nanomaterials during the repair and strengthening of ancient wooden structures. Using the method of this article, through the analysis of experimental data, we understand the role of the strength of nanomaterials during the repair and strengthening of ancient wooden structures, and found that the strength of nanomaterials plays an important role when repairing and strengthening the ancient wooden structures. Combined with the experimental data, it is analyzed that the effect of the value of nanomaterial strength when repairing and strengthening the ancient building wood structure is 58%. The research results show that the value of nanomaterial strength when repairing and strengthening the ancient building wood structure has an important role.